Psychological assessment of psychological well being in Argentine adolescent students - Martina Casullo, María (2000)
The main goal of this study is to develop a brief scale to assess perceived well being in adolescentpopulation. Besides verifying psychometric properties, we identified individual differences between genders, context and age. Participants were adolescent students recruited in three different areas of Argentina (Metropolitan area -Buenos Aires-, Norwest area- Tucuman- and Southwest area Patagonia- ). aged 13 Th. 18. Instruments administered consisted of BIEPS (well being scale) other classics instruments to assess life satisfaction (SWLS and D-T) anda symptom check list (SLC- 90). Results show that classic instruments to assess well being resulted in less reliable instruments to assess perceived life satisfaction considering other theories. Gender, age and context don't seem to affect subjective perception of psychological well being.